Cambridge IGCES O'Level Computer Science - "Watson, David" (Hodder Education group: London, 2021)
This title is endorsed by Cambridge Assessment International Education to support the full syllabus for examination from 2023. Benefit from the knowledge of our renowned expert authors to navigate through the content of the updated Cambridge IGCSET and O Level Computer Science syllabuses (0478/0984/2210). - Develop computational thinking and problem-solving skills: clearly explained concepts are followed by opportunities to implement in the programming language of choice. - Build an understanding of computer systems and associated technologies: carefully prepared worked examples explain new id
Keywords: Computer science-Textbook